Autoclaved Tumor Bone for Skeletal Reconstruction in Paediatric Patients: A Low Cost Alternative in Developing Countries. (18th December 2013) - Umer, Masood; Umer, Hafiz Muhammad; Qadir, Irfan; Rashid, Haroon; Awan, Rabia; Askari, Raza; Ashraf, Shamvil
Abstract : We reviewed in this series forty patients of pediatric age who underwent resection for malignant tumors of musculoskeletal system followed by biological reconstruction. Our surgical procedure for reconstruction included (1) wide en bloc resection of the tumor; (2) curettage of tumor from the resected bone; (3) autoclaving for 8 minutes (4) bone grafting from the fibula (both vascularized and nonvascularized fibular grafts used); (5) reimplantation of the autoclaved bone into the host bone defect and fixation with plates. Functional evaluation was done using MSTS scoring system. At final followup of at least 18 months (mean 29.2 months), 31 patients had recovered without any complications. Thirty-eight patients successfully achieved a solid bony union between the graft and recipient bone. Three patients had surgical site infection. They were managed with wound debridement and flap coverage of the defect. Local recurrence and nonunion occurred in two patients each. One patient underwent disarticulation at hip due to extensive local disease and one died of metastasis. For patients with non-union, revision procedure with bone graft and compression plates was successfully used. The use of autoclaved tumor grafts provides a limb salvage option that is inexpensive and independent of external resources and is a viable option for musculoskeletal tumor management in developing countries.